2011
DOI: 10.1063/1.3660399
|View full text |Cite
|
Sign up to set email alerts
|

Negative ions: The overlooked species in thin film growth by pulsed laser deposition

Abstract: Plasma plume species from a ceramic La 0.4 Ca 0.6 MnO 3 target were studied by plasma mass spectrometry as a function of laser fluence, background gas, and deposition pressure to understand the interplay between plasma composition and oxide thin film growth by pulsed laser deposition. The plume composition reveals a significant contribution of up to 24% of negative ions, most notably using a N 2 O background. The significance of negative ions for thin film growth is shown for La 0.4 Ca 0.6 MnO 3 films grown in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…More recently, an improvement of film quality has been reported when ablating La 0.6 Ca 0.4 MnO 3 in the presence of N 2 O gas that coincides with the largest amount of negatively charged oxygen species [12,13]. However, these works show on the one hand that the amount of negatively charged species is less important and almost non-relevant in O 2 and vacuum, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, an improvement of film quality has been reported when ablating La 0.6 Ca 0.4 MnO 3 in the presence of N 2 O gas that coincides with the largest amount of negatively charged oxygen species [12,13]. However, these works show on the one hand that the amount of negatively charged species is less important and almost non-relevant in O 2 and vacuum, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Moderation of the kinetic energy of plasma species with increasing pressure, and the formation of negative species may improve film growth and crystallinity. 20 Analyzing these correlations using mass spectrometry, 20-24 emission/ absorption spectroscopy, [25][26][27] and plasma imaging 13,28 have led to an improved understanding of the physical properties of the laser induced plasma. A more quantitative approach to capture the simultaneously ongoing chemical aspects, in particular the reaction of plasma species with a background gas and to reliably determine the film composition, is still missing.…”
mentioning
confidence: 99%
“…To the best of our knowledge it has not yet been used for the PLD growth of LSCO thin films. Nevertheless, it has recently been demonstrated that thin LCMO films grown with PLD in N 2 O atmosphere have a higher oxygen content and a superior crystalline quality than those grown in O 2 environment 18 . In this manuscript we describe the N 2 O assisted PLD growth of La superlattices with a repetition number of X = 1, 3, 5, 7 and 9 bilayers (in the following we refer to them as X BL samples) have been grown in a PLD chamber (SURFACE-TEC GmbH), equipped with an excimer KrF laser source (λ = 248 nm, t s = 25 ns) and an infrared laser (JENOPTIK, JOLD-140-CAXF-6A) for heating the substrate.…”
Section: Introductionmentioning
confidence: 99%